Pendekatan Culturally Responsive Teaching (CRT) Berbantuan Media Puzzle Jigsaw Untuk Meningkatkan Kemampuan Pemecahan Masalah Pada Mata Pelajaran Ips Tingkat SMP - Wirdatul Ahya; Rambang Muharramsyah; Sumanti Sumanti (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to develop and examine the feasibility, practicality, and effectiveness of Culturally Responsive Teaching (CRT)-based Jigsaw Puzzle media in improving junior high school students' problem-solving skills in Social Studies learning. The research employed a Research and Development (R&D) design using the DDDE model, consisting of Decide, Design, Develop, and Evaluate stages. The participants involved material experts, media experts, language experts, one Social Studies teacher, and 32 ninth-grade students of SMP Negeri 2 Sawang. Data were collected through validation sheets, teacher and student response questionnaires, observation, and problem-solving tests. Quantitative data were analyzed using percentages, normality testing, the Wilcoxon signed-rank test, and N-Gain, while qualitative data were analyzed descriptively based on expert suggestions and field notes. The results showed that the media was highly feasible, with validation scores of 86% from material experts, 90% from media experts, and 94% from language experts. Student and teacher responses reached 86% and 93%, respectively, indicating a very positive level of practicality. The mean score increased from 61.90 in the pretest to 84.84 in the posttest. Since the pretest data were not normally distributed, the Wilcoxon test was applied and showed a significant difference between pretest and posttest scores (p = 0.000). The average N-Gain score was 0.5765, categorized as moderate. These findings indicate that CRT-based Jigsaw Puzzle media is feasible, practical, and moderately effective in supporting contextual Social Studies learning and improving students' problem-solving skills.